Cranial anatomy of the predatory actinopterygian Brazilichthys macrognathus from the Permian (Cisuralian) Pedra de Fogo Formation, Parnaíba Basin, Brazil. Issue 3 (4th May 2019) - Figueroa, Rodrigo T.; Friedman, Matt; Gallo, Valéria
ABSTRACT: Brazilichthys macrognathus is the only named actinopterygian from the Permian (Cisuralian) Pedra de Fogo Formation of northeastern Brazil, in which it is represented by a single three-dimensionally preserved, but incompletely described, skull of unclear systematic placement. We used X-ray micro-computed tomography (µCT) to redescribe its anatomy, in particular parts of the internal skeleton, and assess its phylogenetic affinities. We correct errors in the original description, including the number of infraorbital bones and the misidentification of the dermosphenotic as sclerotic ossifications. These reinterpretations of external anatomy are accompanied by new data on internal structure, including the palate, the parasphenoid, and the branchial and hyoid arches. A maximum parsimony analysis of anatomical data resolves Brazilichthys as a stem actinopterygian, crownward of all Devonian species. This placement is supported by the absence of a dermosphenotic posterior ramus and the presence of opercular process of the hyomandibula. A similar placement is suggested by a Bayesian analysis of the same data set, although relationships throughout the tree are less resolved. Our results reject previous interpretations of Brazilichthys as a relative of Birgeriidae, a Triassic group traditionally placed within the actinopterygian crown. Although Acrolepis is too poorly known to be included in our analysis, we also reject relationship between that taxon and Brazilichthys, because their only shared similarities appear to be broadly distributed among early actinopterygians.